Effectiveness of Derris Scandens (Roxb.) Benth. (Thaowan Priang) in Elderly Patients with Knee Osteoarthritis. - คงล้อมญาติ, จุไรรัตน์; คุณพระ, รัตติกาล (Journal of Preventive Medicine Association of Thailand, 2020)
This study aimed to compare efficacy of diclofenac and Thaowan priang (Derris scandens (Roxb.) Benth.) in treating osteoarthritis in elderly. The severity of osteoarthritis of knee was screened using The Oxford Knee Score. Sixty patients who met the inclusion criteria were equally divided into 2 groups receiving diclofenac 25 mg or Thaowan priang capsule 500 mg three times per day for ten days. Then the patients’ quality of life were evaluated with a WOMAC questionnaire consisting of 3 subscales: pain, stiffness and physical function. The result shows that Thaowan priang was effective in improving the quality of life; reducing pain, stiffness and improving physical function. There were no differences in the mean WOMAC score, stiffness and physical function in the patients treated with diclofenac and Thaowan priang. However, diclofenac was significantly more effective than Thaowan priang in reducing pain. GI irritation effect was observed with diclofenac 7.14% but not with Thaowan priang.